THE NEEDS AND PROBLEMS OF NURSING EDUCATION FOR QUALITY AND PATIENT SAFETY: COMMUNICATION IN NURSING PRACTICE - Thawitsri, Nuanla-or; Suwannatthachote, Praweenya; Vanicharoenchai, Vorawan (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
Communication in nursing practice is essential for the efficiency of patient care because the performance of the role and duty of a nurse has a direct effect on the quality of patient care and recovery. Nurses need to develop the ability to communicate in nursing practice since the start of being a nursing student in order to be able to apply their knowledge and skills to the nursing practice more efficiently, which can reduce the risk and errors caused by communication, and lead to better nursing quality and patient safety. Therefore, teaching in nursing should pay attention to and cultivate students' communication skills. The objectives of this study were 1) to study and analyze the needs and the state teaching and communication problems in nursing practice. 2) To gather information about teaching and learning methods, including case study and computer-supported collaborative learning, as a guideline to enhance nursing students’ communication abilities in the nursing practice. This research was a qualitative study that its data were collected by using group discussions and in-depth interviews. The key informants were thirty people, purposively selected from professional nurses who were eleven mentors, nine nurse educators, five nursing instructors, two experts in education and quality assurance, and three technology and media experts. Qualitative data were analyzed using content analysis and the Priority Needs Index. The research findings were: 1) Nursing students currently lack an understanding of the principles and techniques of excellent communication resulting in lower confidence and often unable to effectively communicate when caring for patients and working with multidisciplinary professionals, caused by a scarcity of knowledge, skill, and experience in nursing communication and interprofessional collaborative practice. 2) Teaching approaches to enhance nursing students’ communication ability involves instructors motivating learners to realize the importance of effective nursing communication, which was performed through instruction and the use of real or simulated clinical scenarios. Moreover, allocating sufficient opportunity for nursing students to be able to repeatedly practice, review, reflect, summarize, share, and integrate knowledge applicable to their new communication situations in nursing practice along with the use of technology also helps supporting communication and collaboration among nursing students.